PENGARUH PENDEKATAN BEHAVIORISME SEBAGAI UPAYA MENINGKATKAN RASA PERCAYA DIRI PENYANDANG DISABILITAS SENSORIK NETRA - Heny Kristiana Rahmawati (Universitas Pahlawan Tuanku Tambusai, 2022)
This research aims to. First, to find out the difference in the average value of the pre-test and post-test experiments, the effect of behavioral counseling on the self-confidence of persons with visually impaired persons at the Pendowo Kudus Pendowo Kudus Social Service Center for Sensory Disabilities (PPPSDSN). And second, to find out whether behavioral counseling has an effect on increasing the self-confidence of persons with visually impaired persons at the Pendowo Kudus Pendowo Kudus Social Services Center for Sensory Disabilities. This research is a quantitative category. The design used in this study is a pre-experiment with a one group pretest posttest design. The sample in this study uses a non-probability technique, namely a sample that does not provide equal opportunities or opportunities for each population to be selected as a sample, using purposive sampling, the research instrument uses a questionnaire, then the data analysis used is the T-test sampling (paired sample). ). T-test) with the help of SPSS version 20.00. The results of this study indicate: First, there is a significant difference in self-confidence of people with visual impairment before and before being given treatment (treatment) through behavior which can be seen from the difference in the average score of pretest 51.8 and posttest 82.8. Second, the results of the hypothesis test also show that the value of sig (2-tailed) is 0.000 < 0.05, which means Ho is rejected and Ha is accepted, so it can be concluded that behavioral counseling has an effect on increasing the self-confidence of people with visually impaired persons at Panti Social Services with Disabilities. Sensory Netra (PPPSDSN) Pendowo Kudus. Keywords: Behavioral Counseling, Self Confidence, Blind Sensory Disabilities